Comparison Of Surgical Outcomes Of 360° Circumferential Trabeculotomy Versus Sectoral Excisional Goniotomy With The Kahook Dual Blade At 6 Months - Hirabayashi MT (Dove Medical Press, 2019)
Matthew T Hirabayashi,1 Dayeong Lee,1 Joshua T King,1 Samuel Thomsen,1,2 Jella A An1,2 1University of Missouri Columbia School of Medicine, Columbia, MO, USA; 2Department of Ophthalmology, Mason Eye Institute, University of Missouri School of Medicine, Columbia, MO, USACorrespondence: Jella A AnDepartment of Ophthalmology, University of Missouri Columbia, 3215 Wingate Court, Columbia, MO 65201, USATel +1 573 884 1311Fax +1 573 884 3330Email anja@health.missouri.eduPurpose: To compare reductions in intraocular pressure (IOP) and IOP-lowering medication use following sectoral excisional goniotomy with the Kahook Dual Blade (KDB) or 360° trabeculotomy (via either Trab360 or gonioscopy-assisted transluminal trabeculotomy [GATT]) in eyes with open-angle glaucoma (OAG) undergoing phacoemulsification cataract surgery.Methods: A retrospective review was conducted to collect data from adult subjects with early to advanced primary or secondary OAG undergoing phacoemulsification combined with either KDB or 360° trabeculotomy (Trab360 or GATT) between August 1, 2016 and July 30, 2018 for which 6-month follow-up was available. Data collected included IOP, glaucoma medications, adverse events, and additional IOP-lowering procedures. The primary outcome measure was surgical success (≥20% IOP or ≥1 medication reduction without additional IOP-lowering procedures) at 6 months.Results: Data were collected from 74 eyes of 61 subjects undergoing KDB excisional goniotomy and 27 eyes of 25 subjects undergoing 360° trabeculotomy (19 eyes of 17 subjects undergoing Trab360 and 8 eyes of 8 subjects undergoing GATT). At 6 months, 81.7% (58/71) of KDB eyes and 84.6% (22/26) of 360° trabeculotomy eyes achieved surgical successes (P=0.737). Mean IOP reductions and medication reductions were similar between groups at 6 months. However, more eyes undergoing KDB than Trab360/GATT achieved target IOP ≤18 mmHg (80.0% [56/70] vs 59.3% [16/27], P=0.040) and ≤15 mmHg (61.4% [43/70] vs 25.9% [7/27], P=0.003) without further IOP-lowering interventions at 6 months. The nature and frequency of adverse events were similar between groups.Conclusions: Both KDB and Trab360 or GATT procedures similarly lowered both IOP and the need for IOP-lowering medications during the first 6 postoperative months. More eyes undergoing KDB excisional goniotomy than 360° trabeculotomy attained target IOP ≤18 mmHg and ≤15 mmHg at 6 months. A full 360° trabecular bypass may not be necessary to achieve maximal efficacy from this class of micro-invasive glaucoma procedures.Keywords: Kahook Dual Blade, goniotomy, Trab360, GATT, MIGS